Personel recovery in depression : the role of peer support in Malaysia - Min, Oon Yen (2021)
Rising depression burden of disease on individuals themselves and society at large has spurred efforts to uncover appropriate recovery-oriented practices. In Malaysia, the role of peer support has not been adequately understood nor implemented into frameworks of recovery for depression despite its efficacy shown in overseas studies. This study investigates service users’ experiences of personal recovery and its conceptualisations, processes and outcomes through peer support, and peer support mechanisms that support personal recovery in depression. A qualitative study design was undertaken, and guided by the constructivist grounded theory methods with a pragmatic approach. Semi-structured interviews were conducted with 9 participants; verbatim transcripts were coded and analysed with a constant comparison method, until theoretical saturation was achieved. The analysis showed that personal recovery is conceptualised as a journey through the four prominent stages of (1) awareness, (2) acceptance, (3) adaptation and (4) advancement, generated by intrapersonal and interpersonal processes when service users are engaged in peer support mechanism consisting of identity, relation and impact dimensions. The emergent concepts were integrated to construct the Peer Support Depression Recovery Framework, which consists of the processes and outcomes of personal recovery in depression and its relevant peer support mechanisms. As such, peer support in Malaysia is experienced as helpful for service users to catalyse personal recovery in depression, similar to preceding studies. The implications and limitations of this study are discussed along with recommendations for future studies.